Spatiotemporal analysis of a final-state shape resonance in interferometric photoemission from Cu(111) surfaces - Ambrosio, M. J.; Thumm, U. (My University, 2019)
Photoemission from solid targets includes the excitation and motion of electrons inside the substrate, followed by their propagation in vacuum and detection. It thus depends on the electronic band structure of the solid in the two distinct spectral domains of bound initial and continuum final states. While the imprint of the static (initial-state) valence electronic structure of solids on photoemission spectra is routinely examined in standard photoemission spectroscopy in the energy domain, state-of-the-art time-resolved photoelectron spectroscopy allows, in addition, the scrutiny of photoelectron propagation in the electronic continuum. Within a quantum-mechanical model for attosecond time-resolved interferometric photoelectron emission from solids, we calculated photoemission spectra as a function of the delay between the exciting primary attosecond pulse train and assisting infrared (IR) laser pulse. Accounting for final-state interactions of the photoelectron with the IR laser electric field and the periodic substrate, our numerical results for interferometric photoemission from the 3d-valence band of Cu(111) surfaces show a striking resonantly enhanced sideband yield at photoelectron kinetic energies near 24eV, in conjunction with a pronounced increase of the photoelectron wave-function amplitude inside the solid on a length scale of a few nanometers. This resonant shift of final-state photoelectron-probability density towards the bulk can be interpreted as an increase in the photoelectron propagation time in the solid and is commensurate with the resonantly enhanced spectral sideband-phase shifts observed in recent two-pathway two-photon interference spectra by Kasmi et al. [Optica 4, 1492 (2017)].